RANCANGAN STRATEGI PENGEMBANGAN PRODUKSI, PRODUKTIVITAS DAN MUTU KOMODITAS KOPI ROBUSTA DI KECAMATAN SILO KABUPATEN JEMBER - Djoko Soejono (University of Jember, 2012)
The purpose of the study was to determine (1) the condition of the real farms by farmers in selected areas; (2) the characteristics of farm income in selected areas; (3) efforts to increase production, productivity and quality of coffee commodity; and (4) recommendations to increase production, productivity and quality of coffee commodity. The supporting analysis tools were used: (1) analysis of costs , revenues and earnings; (2) descriptive analysis; and (3) force fields analysis. Coffee crop farming activities by applying Sidomulyo Village coffee farmers planting multiple cropping system, implemented by planting plants in garden coffee sidelines near the coffee plants of economic value as well as shade plants such as plants apukat coffee, coconut, banana, yam, sengon and mahogany. Coffee processing logs into the system in the form of coffee ose, divided into two ways , namely wet processing systems and processing systems to dry. Average revenue per hectare coffee farm in 2010 for coffee if the system dry with around Rp 15.750.000 per Ha. Revenue in the system if the wet spring (HS) is Rp 20.325.000 per ha and if the form OSE generated revenues of approximately Rp 30.075.000 per Ha. There is a difference in income between the system if the system is semi-dry if wet, which if wet systems provide income (profit) is relatively higher than dry system. Difference in difference with semi- wet (HS) is Rp 4.575.000 per ha and if wet (OSE) Rp 14.325.000 per Ha. In addition, there are differences in income between coffee system if wet HS and OSE, which is 9.750.000 per ha or 67,6 percent. Efforts to increase production , productivity and quality should still consider the four (4) important factors , namely : (1) input factors are controlled ; (2) the input factor that is not controlled ; (3) the desired output factors ; and (4) factors that are not desired outputs Keywords : Strategy, Production, Productivity and Quality of Coffee